The Local Wisdom and Educational Values in Kurung-Kurung Music of the Dayak Meratus Loksado: English - Muhammad Najamudin; Maryanto Maryanto; Dedy Ari Nugroho (Gondang: Jurnal Seni dan Budaya, 2026)
This study aims to uncover the educational values ​​contained in the traditional kurung-kurung music of the Dayak Meratus community in Loksado, South Kalimantan. The kurung-kurung music, played in an ensemble with bamboo instruments, serves not only as entertainment or a complement to traditional ceremonies, but also as a means of transmitting cultural values ​​through an ethnopedagogical approach. This study used a descriptive qualitative method with data collection techniques in the form of participatory observation, in-depth interviews, and documentation. Analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that kurung-kurung music contains important educational values ​​for the community, namely: (1) discipline, (2) awareness of environmental conservation, (3) obedience to leaders, (4) tolerance, and (5) mutual cooperation. These values ​​are rooted in the local wisdom of the Meratus agrarian community that prioritizes social and ecological harmony. Thus, kurung-kurung music not only preserves cultural identity, but also functions as a medium for character education that is relevant to the needs of the younger generation in the modern era.